Thirsty [videorecording (DVD)] - Abt, Emily; Neumann, Jamie, 1981-; Kang, Sung, 1972-; Birch, Thora; Sedgwick, Kyra (Gravitas Ventures, 2024)
A tenacious defense attorney embarks on a high stakes campaign to beat the incumbent mayor of Oakland. As election day approaches, she must reconcile the seduction of the political game with her own moral compass or risk losing it all.